A proteomic analysis of C-reactive protein stimulated THP-1 monocytes - Ayhan Mustafa; Lancaster Graeme I; Oliva Karen; Habersberger Jonathon; Eisenhardt Steffen U; Woollard Kevin J; Bannasch Holger; Rice Greg E; Peter Karlheinz (Proteome Science, 2011)
Abstract Background C-reactive protein (CRP) is a predictor of cardiovascular risk. It circulates as a pentameric protein in plasma. Recently, a potential dissociation mechanism from the disc-shaped pentameric CRP (pCRP) into single monomers (monomeric or mCRP) has been described. It has been shown that mCRP has strong pro-inflammatory effects on monocytes. To further define the role of mCRP in determining monocyte phenotype, the effects of CRP isoforms on THP-1 protein expression profiles were determined. The hypothesis to be tested was that mCRP induces specific changes in the protein expression profile of THP-1 cells that differ from that of pCRP. Methods Protein cell lysates from control and mCRP, pCRP or LPS-treated THP-1 cells were displayed using 2-dimensional SDS PAGE and compared. Differentially expressed proteins were identified by MALDI-TOF MS and confirmed by Western blotting. Results mCRP significantly up-regulates ubiquitin-activating enzyme E1, a member of the ubiquitin-proteasome system in THP-1 monocytes. Furthermore, HSP 70, alpha-actinin-4 (ACTN4) and alpha-enolase/enolase 1 were upregulated. The proteomic profile of LPS and pCRP treated monocytes differ significantly from that of mCRP. Conclusion The data obtained in this study support the hypothesis that isoform-specific effects of CRP may differentially regulate the phenotype of monocytes.